Pengaruh Likuiditas, Aktivitas dan Profitabilitas terhadap Pertumbuhan Perusahaan pada Perusahaan LQ 45 Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2020 - kiki wulandari; Irham Lihan (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2022)
This study aims to determine the effect of liquidity, activity and profitability on company growth in LQ 45 companies Listed on the Indonesian Stock Exchange in 2015-2020. The population in this study are LQ 45 manufacturing sub-sector companies listed on the Indonesia Stock Exchange in 2015-2020. The sample of this research is 29 companies selected by purposive sampling method and using multiple regression analysis to test the hypothesis. The measuring instrument of the independent variable is the current ratio, inventory turnover and return on equity, while the dependent variable is asset growth. The conclusion of this research is that the current ratio, inventory turnover and return on equity has a positive effect on company growth with a significance level of 5%.